Kajian Sastra Anak “Biji Semangka Ajaib” dalam Penerapan Pendidikan Karakter Berbasis Biblioterapi Didaktik - Desty Putri Hanifah; Rochyani Lestiyanawati (Jurnal Elementaria Edukasia, 2023)
The purpose of this research is to conduct a study and review of children's literature before the children's literature is given to children or students at school. The surgical approach to children's literature uses a didactic bibliotherapy model or therapy using a book as a medium. Children's literature is considered able to improve the character in a child through the images that are built in the child's subconscious. The more positive images that are built, the more positive character in the child will be. Didactic bibliotherapy is an alternative that can deliver the positive values ​​contained in children's literature. Didactic bibliotherapy can work both preventively and curatively in the development of children's character. This study uses a library research type in conducting a study and review of children's literature. The book that was studied was a children's book entitled “Biji Semangka Ajaib”. This book is a book published by the Ministry of Education and Culture in collaboration with Room to Read. The study and surgery of children's literature before the application of didactic bibliotherapy is very important because it becomes the core of bibliotherapy itself. This children's literature review is used as the basis for applying didactic bibliotherapy both personally and in groups.